2022
DOI: 10.1042/cs20220235
|View full text |Cite
|
Sign up to set email alerts
|

Vascular dysfunction in COVID-19 patients: update on SARS-CoV-2 infection of endothelial cells and the role of long non-coding RNAs

Abstract: Although COVID-19 is primarily a respiratory disease, it may affect also the cardiovascular system. COVID-19 patients with cardiovascular disorder (CVD) develop a more severe disease course with a significantly higher mortality rate than non-CVD patients. A common denominator of CVD is the dysfunction of endothelial cells (ECs), increased vascular permeability, endothelial-to-mesenchymal transition, coagulation, and inflammation. It has been assumed that clinical complications in COVID-19 patients suffering fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 240 publications
0
7
0
Order By: Relevance
“…The mechanism of this “swollen heart” phenomenon may possibly be explained by two scenarios—systemic inflammation and cytokine storm, which can lead to a microvascular dysfunction and an increased permeability or by fluid overload during an infection. The concept of COVID-19 as an endothelial disease is now widely accepted ( 3 , 21 , 22 ), and an increased vascular permeability was documented as an effect of SARS-CoV2 infection of in vitro cultured endothelial cells ( 23 ). The changes in cardiac structure and geometry observed in our study during a 1-year follow-up support the hypothesis of transient myocardial thickening and reversible myocardial oedema in the acute phase of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this “swollen heart” phenomenon may possibly be explained by two scenarios—systemic inflammation and cytokine storm, which can lead to a microvascular dysfunction and an increased permeability or by fluid overload during an infection. The concept of COVID-19 as an endothelial disease is now widely accepted ( 3 , 21 , 22 ), and an increased vascular permeability was documented as an effect of SARS-CoV2 infection of in vitro cultured endothelial cells ( 23 ). The changes in cardiac structure and geometry observed in our study during a 1-year follow-up support the hypothesis of transient myocardial thickening and reversible myocardial oedema in the acute phase of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, like many other viruses, SARS-CoV-2 is thought to modulate mitochondrial dynamics in its own benefit [66][67][68], by sending its genetic material towards the mitochondria to influence ROS production, mitophagy, iron storage, platelet coagulability, and cytokine production stimulation, supporting viral replication [69,70]. Thus, the infection of endothelial cells by SARS-COV-2 might contribute to mitochondrial dysfunction and oxidative stress, key players on the initiation of chronic inflammation and endothelial damage [71]. Drugs targeting mitochondria and/or some of the proteins highlighted here could be considered as potential tools for protecting the endothelium in severe forms of COVID-19 [72].…”
Section: Discussionmentioning
confidence: 99%
“… 48 Studies by Kondo and colleagues have suggested that SARS-CoV-2 may impact hepatic endothelial cells through direct infection; however, endothelial cells have shown resistance to and absence of SARS-CoV-2 infection both in vivo and in vitro . 49 , 50 Despite several studies highlighting how SARS-CoV-2 viral infection can lead to microthrombi, additional studies for how SARS-CoV-2 infection may cause microthrombi within the liver, are still required.…”
Section: Discussionmentioning
confidence: 99%